Penerapan Nilai-Nilai Pendidikan Akhlak Wanita dalam Kitab Maratusholihah Santri Putri di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Irma Susanti (Departement of Mathematics Education, 2024)
This research is motivated by the existence of several female students who are not good in the values ​​of moral education is a conscious effort made by someone through coaching in the field of religion to instill moral values ​​in a person. The focus of the research studied includes: 1) How is the application of the Values ​​of Moral Education in the Maratusolihah Book, the moral aspect to both parents at the Hidayatul Mubtadiin Jati Agung South Lampung Islamic Boarding School?; 2) How is the Application of the Values ​​of Moral Education in the Maratusholihah Book, the moral aspect to the ustadz/ustadzah at the Hidayatul Mubtadiin Jati Agung South Lampung Islamic Boarding School?; This study uses a qualitative method with a descriptive type. The data collection technique uses passive participant observation, semi-structured interviews and document studies. While the data analysis uses qualitative descriptive. With data analysis, namely, data presentation and drawing conclusions. The validity of the data uses conclusions and sources. The results of this study are: 1) The application of the values ​​of moral education in the Maratusholihah book by female students towards their parents has been implemented well, such as being obedient and devoted to their orders, not being rude in their behavior. However, there are some students who have not implemented it towards their parents, there are some female students whose morals are not good. There are still students who still shout at their parents, although they do it unconsciously but it is not allowed; 2) The application of the values ​​of moral education in the Maratusholihah book towards the ustadz/ustadzah at the Islamic Boarding School has been implemented well enough, obedient and polite in their behavior. Of the many students, there are some of them who have not done it optimally, there are still some students who gossip about ustadzah behind their backs and behave impolitely towards teachers and ustadzah.